Politicians under Investigation: The News Media's Effect on the Likelihood of Resignation - Jil Sörensen; Marcel Garz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the effect of news media on the probability of resignation from office of politicians being subject to criminal investigation. Using data on cases in which the political immunity of German representatives was lifted, we find that resignations are more common when the media covers the case intensely. The amounts of this news coverage, in turn, depend on the availability of other newsworthy, exogenous events. Therefore, we instrument for coverage of lifts of immunity with the overall news pressure. We estimate the causal effect and find that a 1 standard deviation increase in the amount of the coverage raises the likelihood of resignation by 22.3 percentage points.
Keywords: K14; L82; P16; 330; news media; political accountability; prosecution; resignation